1998
DOI: 10.1111/j.1525-1446.1998.tb00366.x
|View full text |Cite
|
Sign up to set email alerts
|

The Community Health Nursing Implications of the Self‐Reported Health Status of a Local Homeless Population

Abstract: This study explored the personal characteristics and the health and health-related concerns reported by members of the local homeless population in order to design population-specific health programming. The study also examined whether there were significant differences between homeless who are shelter residents and those who are not. An exploratory descriptive design was used to analyze retrospective data collected by a local County Health Department in interviews of 132 homeless adults. The demographic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Ratner, Johnson, and Jeffery (1998) found that people who rate their health status usually consider only their physical health, so for this study, health status was conceptualized as a physical health variable. Reichenbach, McNamee, and Seibel (1998) grouped descriptive results from an inquiry into the health status of homeless adults into two categories: poor/fair (37%) and good/excellent (63%). Clarke, Williams, Percy, and Kim's (1995) inquiry into the health status of homeless persons produced similar results.…”
Section: Health Status and Fatiguementioning
confidence: 99%
“…Ratner, Johnson, and Jeffery (1998) found that people who rate their health status usually consider only their physical health, so for this study, health status was conceptualized as a physical health variable. Reichenbach, McNamee, and Seibel (1998) grouped descriptive results from an inquiry into the health status of homeless adults into two categories: poor/fair (37%) and good/excellent (63%). Clarke, Williams, Percy, and Kim's (1995) inquiry into the health status of homeless persons produced similar results.…”
Section: Health Status and Fatiguementioning
confidence: 99%
“…Later studies support these findings: White, Tulsky, Dawson, Zolopa, and Moss (1997) reported that homeless individuals with physical or mental health problems were three times more likely than the general population in the United States to rate their health as fair or poor. Wojtusik and White (1998), and Reichenbach, McNamee, and Seibel (1998) also found that in the 37% to 50% of homeless persons self-rating health as fair and poor, most had physical and mental health problems. African Americans in particular report lower health status than Whites (Kington & Smith, 1997) as well as lower levels of well-being (Schulz et al, 2001).…”
Section: Predictors Of Perceived Health Statusmentioning
confidence: 99%